Financial Development and Income Inequality: Is There Any Financial Kuznets Curve in Iran? - Nanthakumar, Loganathan; Muhammad, Shahbaz; Aviral, Tiwari (2015)
This paper deals with the investigation of the relationship between financial development and income inequality in case of Iran. In doing so, we have applied the ARDL bounds testing approach to examine the long-run relationship in the presence of structural break in the series. The unit root properties have been tested by applying Zivot and Andrews (in J Bus Econ Stat 10:251–270, 1992) and Clemente et al. (in Econ Lett 59, 175–182, 1998) structural break tests. The VECM Granger causality approach is used to detect the direction of the causal relationship between financial development and income inequality. Moreover, Greenwood–Jovanovich (GJ) hypothesis has also been tested for Iranian economy. Our results confirm the long run relationship between the variables. Furthermore, financial development reduces income inequality. Economic growth worsens income inequality, but inflation and globalization improve income distribution. Finally, GJ hypothesis is found as well as U-shaped relationship between globalization and income inequality in case of Iran. This study might provide new insights for policy makers to reduce income inequality by making economic growth more fruitful for poor segment of population and directing financial sector to provide access to financial resources of poor individuals at cheaper cost.